Ecology of Glossina fuscipes fuscipes newst. (Diptera: Glossinidae) along lake Victoria shore in South Nyanza. - Oloo, F.P. (University of Nairobi, 1983)
Ecology of Glossina fuscipes fuscipes Newstead was studied with specific reference to temperature, relative humidity, light intensity, resting and breeding sites. The comprehensive study was undertaken to assemble, upgrade and bridge gaps in information on the species which would be used in organizing control programmes against the fly. Hourly temperature and relative humidity taken where the flies were caught along a representative belt transect laid across tsetse fly habitats showed low correlation with catches from or near stationary human-baits during day-time. Temperature apparently o 0 switched biting activity on and off at 20 C and 36 C respectively, but had little influence on activity when it was on.. Light intensity read from photographic exposure meter showed significant positive correlation with hourly catches and seemed to be the main physical factor controlling the fly activity within the temperature range allowing flight. The fly exhibited one diurnal activity peak between 0815 and 1315 h with climax at 1045 h